2017
DOI: 10.14419/ijdr.v5i2.7689
|View full text |Cite
|
Sign up to set email alerts
|

Gingival crevicular fluid level of soluble triggering recep-tor expressed on myeloid cells-1(strem-1) in periodontal health and disease: a case-control study

Abstract: Background: The Triggering Receptor Expressed On Myeloid Cells-1(TREM-1) is a cell-surface receptor of the immunoglobulin superfamily and found to be involved in the amplification of the inflammatory response to various microbial infections, including periodontal diseases. Objectives: The present study was designed to examine gingivalcrevicular fluid(GCF) levels of soluble TREM-1 (sTREM-1) levels in periodontal health and disease as well as evaluate the effect of scaling and/or root planing on the same. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In our study, all the three evaluated biomarkers ("sTREM-1, IL-1β and MMP-8") were found to be elevated in the periodontitis groups compared to the healthy groups. In the Bostanci et al study, 22 they had observed a 3.3-5.6 fold raised salivary sTREM-1 levels in advanced periodontitis cases and similarly, Belibasakis et al in 2014 23 and Surabhigigras et al in 2017 24 reported increased sTREM-1 levels in disease sites and all forms of periodontitis. The results of our study also supports these findings.…”
Section: Discussionmentioning
confidence: 82%
“…In our study, all the three evaluated biomarkers ("sTREM-1, IL-1β and MMP-8") were found to be elevated in the periodontitis groups compared to the healthy groups. In the Bostanci et al study, 22 they had observed a 3.3-5.6 fold raised salivary sTREM-1 levels in advanced periodontitis cases and similarly, Belibasakis et al in 2014 23 and Surabhigigras et al in 2017 24 reported increased sTREM-1 levels in disease sites and all forms of periodontitis. The results of our study also supports these findings.…”
Section: Discussionmentioning
confidence: 82%